Legal Uncertainty in the Establishment of Danantara: A Critical Legal Analysis - Maudy Dea Aditya (Universitas Negeri Surabaya, 2025)
The establishment of the State Investment Agency (Danantara) is a strategic step taken by the Indonesian government to improve the effectiveness and efficiency of state investment management. The main objective of establishing Danantara is to optimise national investment potential and promote long-term sustainable economic growth. However, in its implementation, Danantara faces significant challenges, especially in the legal and regulatory aspects. One of the main challenges is the potential overlap of authority with other institutions such as State-Owned Enterprises (SOEs), the Ministry of Finance, and other investment management entities. The urgency of writing this article lies in the importance of in-depth analysis of the regulations governing Danantara in order to avoid institutional conflicts and ensure transparent, accountable, effective, and efficient investment governance. The method used is normative legal research with a juridical approach, based on literature study and legal document analysis. The results show the need for regulatory harmonisation and strengthening of supervisory mechanisms so that Danantara can function optimally within a clear, coordinated and integrated national legal framework.